Transferrin receptor 2 mitigates periodontitis-driven alveolar bone loss - Lösser, Lennart; Ledesma-Colunga, Maria G.; Sastre, Enrique Andrés; Scholtysek, Carina; Hofbauer, Lorenz C.; Noack, Barbara; Baschant, Ulrike; Rauner, Martina (Journal of Cellular Physiology, 2024)
Periodontitis is associated with significant alveolar bone loss. Patients with iron overload suffer more frequently from periodontitis, however, the underlying mechanisms remain largely elusive. Here, we investigated the role of transferrin receptor 2 (Tfr2), one of the main regulators of iron homeostasis, in the pathogenesis of periodontitis and the dental phenotype under basal conditions in mice. As Tfr2 suppresses osteoclastogenesis, we hypothesized that deficiency of Tfr2 may exacerbate periodontitis-induced bone loss. Mice lacking Tfr2 (Tfr2−/−) and wild-type (Tfr2+/+) littermates were challenged with experimental periodontitis. Mandibles and maxillae were collected for microcomputed tomography and histology analyses. Osteoclast cultures from Tfr2+/+ and Tfr2−/− mice were established and analyzed for differentiation efficiency, by performing messenger RNA expression and protein signaling pathways. After 8 days, Tfr2-deficient mice revealed a more severe course of periodontitis paralleled by higher immune cell infiltration and a higher histological inflammation index than Tfr2+/+ mice. Moreover, Tfr2-deficient mice lost more alveolar bone compared to Tfr2+/+ littermates, an effect that was only partially iron-dependent. Histological analysis revealed a higher number of osteoclasts in the alveolar bone of Tfr2-deficient mice. In line, Tfr2-deficient osteoclastic differentiation ex vivo was faster and more efficient as reflected by a higher number of osteoclasts, a higher expression of osteoclast markers, and an increased resorptive activity. Mechanistically, Tfr2-deficient osteoclasts showed a higher p38-MAPK signaling and inhibition of p38-MAPK signaling in Tfr2-deficient cells reverted osteoclast formation to Tfr2+/+ levels. Taken together, our data indicate that Tfr2 modulates the inflammatory response in periodontitis thereby mitigating effects on alveolar bone loss.
CRIS-Team Scopus Importer:2024-02-02
Keywords: osteoclast; periodontitis; Tfr2